Transcriptional Control of Synaptic Plasticity by Transcription Factor NF-κB - Christian Engelmann; Ronny Haenold (Neural Plasticity)
Activation of nuclear factor kappa B (NF-κB) transcription factors is required for the induction of synaptic plasticity and memory formation. All components of this signaling pathway are localized at synapses, and transcriptionally active NF-κB dimers move to the nucleus to translate synaptic signals into altered gene expression. Neuron-specific inhibition results in altered connectivity of excitatory and inhibitory synapses and functionally in selective learning deficits. Recent research on transgenic mice with impaired or hyperactivated NF-κB gave important insights into plasticity-related target gene expression that is regulated by NF-κB. In this minireview, we update the available data on the role of this transcription factor for learning and memory formation and comment on cross-sectional activation of NF-κB in the aged and diseased brain that may directly or indirectly affect κB-dependent transcription of synaptic genes.